Traditional Chinese Medicine for Coronary Heart Disease: Clinical Evidence and Possible Mechanisms - Zhang, Ke-Jian; Zheng, Qun; Zhu, Peng-Chong; Tong, Qiang; Zhuang, Zhuang; Zhu, Jia-Zhen; Bao, Xiao-Yi; Huang, Yue-Yue; Zheng, Guo-Qing; Wang, Yan (Frontiers in Pharmacology, 2019)
Abstract Coronary heart disease (CHD) remains a major cause of mortality with a huge economic burden on healthcare worldwide. Here, we conducted a systematic review to investigate the efficacy and safety of Chinese herbal medicine (CHM) for CHD based on high-quality randomized controlled trials (RCTs) and summarized its possible mechanisms according to animal-based researches. Twenty-seven eligible studies were identified in 8 database searches from inception to June 2018. The methodological quality was assessed using 7-item checklist recommended by Cochrane Collaboration. All the data were analyzed using Rev-Man 5.3 software. As a result, the score of study quality ranged from 4 to 7 points. Meta-analyses showed CHM can significantly reduce the incidence of myocardial infarction and percutaneous coronary intervention, and cardiovascular mortality (P< 0.05), increase systolic function of heart, the ST-segment depression and clinical efficacy (P< 0.05). Adverse events were reported in 11 studies, and CHMs were well tolerated in patients with CHD. In addition, CHM exerted cardioprotection for CHD, possibly altering multiple signal pathways through anti-inflammatory, anti-oxidation, anti-apoptosis, improving the circulation, and regulating energy metabolism. In conclusion, the evidence available from present study revealed that CHMs are benefit for CHD and are generally safe.